Assessment of testicular stiffness in fertile dogs with shear wave elastography techniques: a pilot study - Zappone, Viola; Iannelli, Nicola Maria; Sinagra, Letizia; Donato, Giulia; Quartuccio, Marco; Cristarella, Santo; De Majo, Massimo; Caspanello, Tiziana (Frontiers in Veterinary Science, 2024)
Ultrasound of the testes is important in the evaluation of breeding dogs, and recently advanced techniques such as Shear Wave Elastography (SWE) have been developed. This study focused on evaluation of normal testicular stiffness in healthy and fertile male dogs, employing both qualitative (2D-SWE) and quantitative (pSWE, 2D-SWE) techniques. Nineteen dogs of various medium-large breeds aged 3.39±2.15 years, and with a history of successful reproduction were included after clinical, B-mode and Doppler ultrasound of testes and prostate, and semen macro and microscopic evaluations. pSWE involved square regions of interest (ROIs) placed at six different points in the testicular parenchyma, while 2D-SWE depicted stiffness with a color scale ranging from blue (soft) to red (stiff), allowing a subsequent quantification of stiffness by the application of 4 round ROIs. The results showed a mean Shear Wave Speed (SWS) of 2.15±0.39 m/s using pSWE, with lower values above the mediastinum compared to below, and in the center of the testis compared to the cranial and caudal poles. 2D-SWE demonstrated a uniform blue pattern in the parenchyma, and a mean SWS of 1.65±0.15 m/s. No significant differences were found between left and right testes, above and below the mediastinum, or among breeds. No correlations were observed between mean SWS and body condition score, age, testicular and prostatic volume. Weight was positively correlated with mean SWS only by 2D-SWE. By performing semen analysis and enrolling only healthy and fertile adult dogs, we ensured both structural and functional integrity of the testes. This pilot study represents a valuable baseline data for testicular stiffness by both pSWE and 2D-SWE with a Mindray US machine in medium-large sized healthy and fertile dogs, pointing out the potential role of SWE in the non-invasive fertility assessment and management of breeding dogs.